2019
DOI: 10.3390/met9111205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment on the Microstructure and Mechanical Properties of a Composite Made of Al-Si-Cu-Mg Aluminum Alloy Reinforced with SiC Particles

Abstract: In this paper, the effect of heat treatment (solution treatment and artificial aging) on the microstructure and properties of as-cast Al5Si1Cu0.5Mg aluminum alloy and its composite reinforced with 1.5 wt.% SiC particles was studied. The results showed that at 520 • C the optimal solution time for the aluminum alloy and its composite is 9 h and 6 h, respectively. After solution treatment, the microstructure of these two materials consists of a uniform distribution of nearly spherical eutectic Si and skeletal γ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…After heat treatment, the ultimate tensile strength (UTS)increased from 104.39 to 143 KN (improved by 37.17%) while the hardness increased from 56.13 to 78.80 HRB (improved by 40.38%). The increase in UTS and HRB was due to the precipitation of phases such as Mg2Si and the strong interfacial bonding strength of the Al-Si eutectic phase (Singh et al, 2016;Li et al, 2019).…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…After heat treatment, the ultimate tensile strength (UTS)increased from 104.39 to 143 KN (improved by 37.17%) while the hardness increased from 56.13 to 78.80 HRB (improved by 40.38%). The increase in UTS and HRB was due to the precipitation of phases such as Mg2Si and the strong interfacial bonding strength of the Al-Si eutectic phase (Singh et al, 2016;Li et al, 2019).…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Cyclic semi-solid heat treatment changed the morphology of iron-rich intermetallic phases to be plate-like and fine plate iron-rich intermetallic phases instead of needle-like iron-rich intermetallic phases observed in as-cast samples. Li et al (2019) studied the effect of heat treatment (solution treatment and artificial ageing) on the microstructure and properties of as-cast Al 5Si1 Cu 0.5Mg aluminium alloy and composite reinforced with 1.5 wt% SiC particles. Results showed that the optimal solution time for the aluminium alloy and its composite was 9 and 6 hours respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Fabrication of carbon film is a hot topic nowadays, and many of the methods are achieved to prepare carbon film, such as, filtered cathodic vacuum arc (FCVA) [1], pulsed plasma-enhanced chemical vapor deposition (PECVD) [2], pulsed laser deposition (PLD) [3] and so on. ECR plasma sputtering system makes the deposition of carbon film under low temperature and low energy possible, it is also effective for attaining high quality carbon films via electron irradiation or ion irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…For MMSF characteristics of the hollow reinforcements such as porosity percentage and wall thickness also affect the mechanical properites 45 . Among the most reported reinforcements for AMC are carbides (SiC, B 4 C, WC, TiC) [46][47][48][49][50][51][52] , oxides (Al 2 O 3 , SiO 2 , TiO 2 , ZrO 2 , Y 2 O 3 , MgO, CeO 2 ) [53][54][55][56][57][58] , nitrides (Si 3 N 4 , BN) [59][60][61] and Carbon Nanotubes (CNTs) [62][63][64][65][66][67] . For the case of syntactic foams there have been mainly reported metallic or ceramics hollow spheres, being Fe, SiC, SiO 2 and Al 2 O 3 the most used [40][41][42][43][44][45][68][69][70][71][72] .…”
Section: Introductionmentioning
confidence: 99%